2017
DOI: 10.3390/rs9070655
|View full text |Cite
|
Sign up to set email alerts
|

Ground Truth of Passive Microwave Radiative Transfer on Vegetated Land Surfaces

Abstract: Abstract:In this paper, we implemented the in-situ observation of surface soil moisture (SSM), vegetation water content (VWC), and microwave brightness temperatures. By analyzing this in-situ observation dataset and the numerical simulation, we investigated the source of the uncertainty of the current algorithms for Advanced Microwave Scanning Radiometer for Earth observation system (AMSR-E) and AMSR2 to retrieve SSM and vegetation dynamics. Our findings are: (1) the microwave radiative transfer at C-band and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 37 publications
(78 reference statements)
3
22
0
Order By: Relevance
“…It should be noted that the performance of the SMAP soil moisture product also exhibited some improvements under the lower vegetation condition, with the ubRMSE dropping from 0.06 m 3 /m 3 to 0.05 m 3 /m 3 and the R rising from 0.45 to 0.53. These results were also consistent with the consensus that the L-band is more sensitive to the surface soil moisture, especially in densely vegetated regions [2,37,56,57]. Figure 12.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It should be noted that the performance of the SMAP soil moisture product also exhibited some improvements under the lower vegetation condition, with the ubRMSE dropping from 0.06 m 3 /m 3 to 0.05 m 3 /m 3 and the R rising from 0.45 to 0.53. These results were also consistent with the consensus that the L-band is more sensitive to the surface soil moisture, especially in densely vegetated regions [2,37,56,57]. Figure 12.…”
Section: Discussionsupporting
confidence: 90%
“…For SMAP, the MD was nearly unaffected by the VWC. These results further indicated that the L-band is less affected by the vegetation and more sensitive to the surface soil moisture [2,37,56,57]. Regarding RMSE and ubRMSE (Figure 13b,c), FY-3C also showed some positive correlation with VWC.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It should be noted that the performance of the SMAP soil moisture product also exhibited some improvements under the lower vegetation condition, with the ubRMSE dropping from 0.06 m 3 /m 3 to 0.05 m 3 /m 3 and the R rising from 0.45 to 0.53. These results were also consistent with the consensus that the L-band is more sensitive to the surface soil moisture, especially in densely vegetated regions [2,37,56,57].…”
Section: Discussionsupporting
confidence: 91%
“…In Site I (0.125°E, 10.125°N; see Figure 1b), annual precipitation is approximately 1,190 (mm/year). In the synthetic truth, LAI varies temporally between 0.5 and 2 so that the site is moderately vegetated and surface soil moisture can be observed from the satellite especially in the dry seasons (see Sawada et al, 2017, for the sensitivity of microwave brightness temperature to surface soil moisture in the vegetated area). Figure 2a shows the response of each parameter to the gap between simulation and observation.…”
Section: 1029/2020jd032688mentioning
confidence: 99%